Analisis kerangka kerja, aliran, dan hambatan rantai pasokan - Terryna Tasya Mizani; Anton Mulyono Azis (Jurnal Manajemen Maranatha, 2021)
This study aims in determining the implementation of supply-chain framework; identifying the flow of goods, money, and information, as well as the problems and factors that influence them. The research object is the supply chain management of two aircrafts at PT Dirgantara Indonesia (Persero). The descriptive analysis method is used with a qualitative approach as the result of interviews and observations to be analyzed to answer the research questions. The results indicate that the running framework consists of nine activities, the existence of a linkage to each flow, where the punctuality of payment by the customer will facilitate the flow of the goods itself, also the timeliness of delivery by suppliers in obtaining materials can shorten production time, flow of goods, and flow of money. Money will not run smoothly without the accurate flow of information and the credibility of the exchange of information. It is expected that all stakeholders need to further improve coordination and collaborate to create products with the right service quality, quantity, time, and place.